THE ENCHANTING SHRINE OF KASHMIR: UNVEILING THE LEGACY OF KHAWAJA HASSAN QARI - Reyaz Ahmad Bhat; Ishfaq Ahmad Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract This paper presents a comprehensive case study exploring the remarkable shrine of Kashmir, focusing on the profound legacy of Khawaja Hassan Qari. The study delves into the historical, cultural, and religious significance of the shrine, shedding light on its enchanting allure and the enduring impact of Khawaja Hassan Qari's contributions. Through extensive research and analysis, this paper aims to unveil the captivating narrative of the shrine and highlight the intricate details of Khawaja Hassan Qari's life and teachings. The findings offer valuable insights into the rich heritage of Kashmir and the spiritual heritage left behind by this revered figure.